Cross-Sectional Study to Determine the Most Common Cause of Breathing Difficulty in Children from 1 Month to 12 Years of Age (Journal of Fatima Jinnah Medical University, 2018)
Background: Breathing difficulties are most commonly encountered in children and potentially life threatening emergency presenting to a hospital. Having significant mortality and morbidity among children the causes of breathing difficulties are on the rise in Pakistan. Objective: Objective of the study was to determine the most common cause of breathing difficulty in children from 1 month and 12 years of age. So as to guide our planning for primary and secondary prevention of those causes to prevent disease in our community Methodology: This was a cross sectional study. 100 patients presented in Children Hospital Lahore emergency with breathing difficulty were selected on the basis of non-probability (purposive) sampling. Study was completed in 3 months. Questionnaire was made to collect data and their detailed history was then taken including symptoms at presentation Results: The common causes of breathing difficulty in our subjects were Pneumonia 40%, bronchitis 29%, Asthma 14%, sepsis 7%, Hyper respiratory distress syndrome 2%, hypercapnia tetani 2%, Diabetic ketoacidosis (DKA) 2%, encephalitis 2%, foreign body obstruction 1%, croup 1%. 2 Conclusion: The most common cause of breathing difficulty in children from 1 month to 12 years of age was Pneumonia
Keywords: Croup, Pneumonia, Bronchitis, DKA.